18F‐Fluorodeoxyglucose positron emission tomography/computed tomography for the detection of recurrent bone and soft tissue sarcoma. Issue 6 (11th December 2012) - Al‐Ibraheem, Akram; Buck, Andreas K.; Benz, Matthias R.; Rudert, Maximilian; Beer, Ambros J.; Mansour, Asem; Pomykala, Kelsey L.; Haller, Bernhard; Juenger, Hendrik; Scheidhauer, Klemens; Schwaiger, Markus; Herrmann, Ken
Abstract BACKGROUND: The clinical utility of modern hybrid imaging modalities for detecting recurrent bone or soft tissue sarcoma remains to be determined. In this report, the authors present a clinical study on the diagnostic accuracy and incremental value of integrated 18F‐fluorodeoxyglucose positron emission tomography/computed tomography (18F‐FDG PET/CT) in patients with a history of sarcoma who have clinically suspected disease recurrence. METHODS: Forty‐three patients who had a history of bone or soft tissue sarcoma and had documented complete remission underwent 18F‐FDG PET/CT. Image analysis was performed independently for 18F‐FDG PET (n = 43) and for contrast‐enhanced spiral CT (CE‐CT) (n = 30) by 2 separate readers, whereas combined 18F‐FDG PET/CT (n = 43) images were analyzed in consensus by both readers. Imaging findings were rated on a 5‐point scale and finally were reported as malignant, benign, or equivocal. Imaging findings were validated either by histopathology (n = 24) or by clinical follow‐up (n = 19). RESULTS: 18F‐FDG PET/CT had greater sensitivity and specificity compared with CE‐CT alone (94% and 92% vs 78% and 67%, respectively), resulting in significantly greater accuracy (93% vs 73%; P = .03). 18F‐FDG PET/CT was particularly superior regarding detection of local recurrence or soft tissue lesions (sensitivity and specificity: 83% and 100% vs 50% and 100%, respectively) or bone metastases (100% and 100% vs 85% and 88%, respectively). CONCLUSIONS: 18F‐FDG PET/CT had greater diagnostic accuracy in the detection of recurrent bone or soft tissue sarcoma compared with CE‐CT alone. The detection of local recurrence was the most evident advantage of 18F‐FDG PET/CT over CE‐CT. Cancer 2013. © 2012 American Cancer Society.